Treatment of classic hairy cell leukemia: targeting minimal residual disease beyond cladribine - Bohn, Jan-Paul; Dietrich, Sascha (Cancers, 2022)
Classic hairy cell leukemia (HCL) is a rare indolent B-cell lymphoproliferative disorder characterized by profound pancytopenia and frequent infectious complications due to progressive infiltration of the bone marrow and spleen. Lacking effective treatment options, affected patients were confronted with a dismal survival prognosis of less than 5 years when the disease was first described in 1958. Tremendous therapeutic advances were accomplished with the introduction of purine analogues such as cladribine in the 1990s, facilitating a near-normal life expectancy in most HCL patients. Nevertheless, nearly all patients eventually relapse and require successive retreatments, while drug-associated myelotoxicity may accumulate and secondary malignancies may evolve. Detection of minimal residual disease (MRD) in a substantial portion of treated patients has become a surrogate for this still limited treatment efficacy. In the last decade, novel biologic insights such as identification of the driver mutation BRAF V600E have initiated the development and clinical investigation of new, chemotherapy-free, targeted drugs in HCL treatment, with encouraging efficacy in early clinical trials aimed at boosting eradication of MRD while optimizing drug tolerability. This review summarizes current clinical trials investigating treatment strategies beyond purine analogues in HCL and discusses clinically relevant obstacles still to overcome.